Risk disclosure and corporate cash holdings - Issal Haj-Salem; Khaled Hussainey (Journal of Risk and Financial Management, 2021)
In this paper, we extend corporate disclosure and corporate cash holdings literature by testing whether corporate voluntary risk disclosure affects corporate cash holdings for a sample of Tunisian non-financial listed companies. As a measure of risk disclosure, we use manual content analysis to count the number of risk-related sentences in the narrative sections of corporate annual reports. As a measure of corporate cash holdings, we use the ratio of cash and cash equivalent over the total assets. Using a sample of 140 firm-year observations for the period of 2008-2013, we find that corporate risk disclosure has a negative impact on corporate cash holdings. Our results are consistent with agency, legitimacy and impression management theories. Our paper adds to the existing literature by being the first empirical evidence for the impact of risk disclosure on cash holdings. Our findings offer policy implications relevant for the current debate on the reliability of narrative risk disclosure and whether managers inform or obfuscate stakeholders by disclosing more risk-related information in their annual report narratives.
Keywords: 330; cash holdings; content analysis; risk disclosure; Tunisian listed companies